The Effect of Combined Cutaneous Stimulation (Massage) and Lavender Aromatherapy on Sleep Quality in Patients with Diabetes Mellitus - Sugiyarti Sugiyarti; Mohammad Arifin Noor; Suyanto Suyanto (International Journal Of Health Science, 2026)
Diabetes Mellitus (DM) is a chronic disease often accompanied by sleep disturbances, which can worsen the patient's physiological and psychological conditions. Non-pharmacological interventions such as cutaneous stimulation and lavender aromatherapy are known to increase relaxation and improve sleep quality. This study aims to determine the effect of a combination of cutaneous stimulation and lavender aromatherapy on the sleep quality of DM patients. This study used a pre-experimental design with a one-group pretest–posttest approach in 38 outpatient DM patients selected using a purposive sampling technique. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). The intervention was administered for seven consecutive days. Data analysis was performed using the Wilcoxon Signed Ranks Test. The results showed that before the intervention, most respondents had poor sleep quality (97.4%), whereas after the intervention, the majority of respondents experienced an improvement in sleep quality to good (81.6%). The Wilcoxon test results showed a p value = 0.001 (p < 0.05), indicating a significant difference between PSQI scores before and after the intervention. Thus, the combination of cutaneous stimulation and lavender aromatherapy has been proven effective in improving the sleep quality of Diabetes Mellitus patients.